Investigation of multistage injection strategies in a DISI engine fueled with methane under stratified charge lean combustion conditions - Firat, Mujdat (Wiley, 2020)
A three-dimensional numerical study has been performed to study combustion and emission of methane in a stratified charge direct injection spark ignition engines under the multistage injection strategies. Firstly, the combustion and emission characteristics of a single-injection strategy were investigated, and then the effects of two-stage and three-stage injection strategies of the injected fuel on combustion and emissions were analyzed. This simulation was run from intake valve opening to exhaust valve opening under stratified charge conditions using the ANSYS Forte numerical software. The Discrete Particle Ignition Kernel Flame model was used to investigate the ignition process and also the combustion and flame propagation were simulated with the G-equation model. The numerical results show that the multistage injection strategies achieve a significant improvement in the cylinder pressure and combustion efficiency, while reducing NOx, CO, and unburned hydrocarbon emissions compared to single-injection strategy under stratified charge conditions. Also, the efficient multistage injection strategies enhanced the benefits of the emission reduction in the stratified lean combustion with additional increases of combustion efficient.
Keywords: 3D CFD simulation; methane; multistage injection; spark ignition; stratified charge engines